The European Banks' Role in the Financial Crisis of 2007-8: A Critical Assessment - Photis Lysandrou (City, University of London, City Political Economy Research Centre (CITYPERC), 2022)
Since the outbreak of the financial crisis in 2007, opinion has been divided over whether its root cause was credit arbitrage or safe asset demand. New research on the European banks' role in the crisis may finally help to resolve the issue. Far from being peripheral players in the crisis, European banks were deeply implicated in its causal origins as evidenced by their activities in the two US debt markets that were at the heart of the crisis: those for collateralised debt obligations (CDOs) and for asset backed commercial paper (ABCP). These activities would seem to lend weight to the credit arbitrage story, a conclusion that has been reached by several authors. However, it is a conclusion only made possible by ignoring the connection between the federal funds rate and the rate of ABCP demand from the institutional money market mutual funds (MMMFs) in the pre-crisis era. This paper argues that when this connection is closely examined, it turns out that the evidence surrounding the European banks' role in the financial crisis gives greater weight to the safe asset demand explanation of the crisis.
Keywords: G10; F20; 330; European banks; financial crisis; US debt securities markets; US asset backed commercial paper; safe asset demand; federal funds rate; institutional MMMFs